Suppression of Time Delay Signature Based on Brillouin Backscattering of Chaotic Laser - Jianzhong Zhang; Changkun Feng; Mingjiang Zhang; Yi Liu; Yongning Zhang (IEEE Photonics Journal)
A new method by utilizing Brillouin backscattering of optical fiber to suppress the time delay signature (TDS) of an external cavity semiconductor laser is proposed and experimentally demonstrated. When the average power of the injected chaotic laser is within the range of 400–1500 mW, the TDS can be significantly suppressed with the G.655 fiber of the 0.5, 2, 4.5, or 6 km length. The G.652 fiber has the same TDS suppression effect with the G.655 fiber. The TDS suppression effect is relatively stable among a number of measurements ranging from 1 to 50. Moreover, the TDS suppression has nothing to do with the length of the chaotic series by employing the Brillouin backscattering method.